2016
DOI: 10.1149/2.0941702jes
|View full text |Cite
|
Sign up to set email alerts
|

Metal Sulfide-Blended Sulfur Cathodes in High Energy Lithium-Sulfur Cells

Abstract: Lithium-sulfur cells exhibit poor cycle life, due to the well-known 'polysulfide shuttle' enabled by the dissolution of the sulfur reduction products in organic electrolyte. Different strategies have been implemented to reduce the shuttle effects, with limited success, especially through use of low sulfur loadings (1-2 mg/cm 2 ). Dense electrodes with high sulfur loadings are essential for high energy cells, however, such electrodes experience more serious polysulfide effects. In this paper, we describe the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 115 publications
(144 reference statements)
1
32
0
Order By: Relevance
“…XPS was applied to interpret the subtle local interaction between CNT@TiO 2−x and Li 2 S 6 . [33] The presence of TiS bonds was also verified by the lower Ti 2p bands of CNT@TiO 2−x -Li 2 S 6 than CNT@TiO 2−x ( Figure S14A, Supporting Information). The peak located at 161.7 and 163.3 eV can be attributed to terminal (S T −1 ) and bridging sulfur (S B 0 ), respectively.…”
Section: Resultsmentioning
confidence: 79%
“…XPS was applied to interpret the subtle local interaction between CNT@TiO 2−x and Li 2 S 6 . [33] The presence of TiS bonds was also verified by the lower Ti 2p bands of CNT@TiO 2−x -Li 2 S 6 than CNT@TiO 2−x ( Figure S14A, Supporting Information). The peak located at 161.7 and 163.3 eV can be attributed to terminal (S T −1 ) and bridging sulfur (S B 0 ), respectively.…”
Section: Resultsmentioning
confidence: 79%
“…Although it was demonstrated that the addition of commercial, bulk MoS 2 showed improvements in rate capability and capacity retention, the morphology and physical properties of the MoS 2 additive were not modified or controlled. Another report on using a related method of adding either commercially available MoS 2 or TiS 2 to electrode slurries also showed significant improvements during electrochemical testing, including increased sulfur utilization and Coulombic efficiency . These prior reports achieved significant gains with the incorporation of micron‐scale commercially available MoS 2 materials.…”
Section: Introductionmentioning
confidence: 99%
“…Another report on using ar elatedm ethodo f adding either commercially available MoS 2 or TiS 2 to electrode slurriesa lso showed significant improvements during electrochemicaltesting, including increased sulfur utilization and Coulombic efficiency. [45] These prior reports achieved significant gains with the incorporation of micron-scale commercially availableM oS 2 materials. Here we complementt hese prior reports with as ystematic study of synthesized nanosheet materials with controlled defect structures.…”
Section: Introductionmentioning
confidence: 99%
“…These approaches have issues affectingt heir viability.F irst, they involvet he use of ap ure hydrogen reduction environment and requireh igh reduction temperatures that promote the sintering of nanoparticles (NPs). [42] These limitations can be alleviated by integrating metal oxide NPs into lightweight conductive carbon matrices and rationally controlling nanoscale MagnØli phases concurrently. [41] Pure metal oxide cathodes are prone to pulverization,a nd cells assembled from these cathodes also require ah igh concentration of electrolyte to realize good performance, which is not appropriate for high gravimetric capacities.…”
Section: Introductionmentioning
confidence: 99%
“…[41] Pure metal oxide cathodes are prone to pulverization,a nd cells assembled from these cathodes also require ah igh concentration of electrolyte to realize good performance, which is not appropriate for high gravimetric capacities. [42] These limitations can be alleviated by integrating metal oxide NPs into lightweight conductive carbon matrices and rationally controlling nanoscale MagnØli phases concurrently.…”
Section: Introductionmentioning
confidence: 99%